Discovery of functionally selective C5aR2 ligands: novel modulators of C5a signalling. Issue 8 (17th May 2016) - Croker, Daniel E; Monk, Peter N; Halai, Reena; Kaeslin, Geraldine; Schofield, Zoe; Wu, Mike CL; Clark, Richard J; Blaskovich, Mark AT; Morikis, Dimitrios; Floudas, Christodoulos A; Cooper, Matthew A; Woodruff, Trent M
Abstract : The complement cascade is comprised of a highly sophisticated network of innate immune proteins that are activated in response to invading pathogens or tissue injury. The complement activation peptide, C5a, binds two seven transmembrane receptors, namely the C5a receptor 1 (C5aR1) and C5a receptor 2 (C5aR2, or C5L2). C5aR2 is a non‐G‐protein‐signalling receptor whose biological role remains controversial. Some of this controversy arises owing to the lack of selective ligands for C5aR2. In this study, a library of 61 peptides based on the C‐terminus of C5a was assayed for the ability to selectively modulate C5aR2 function. Two ligands (P32 and P59) were identified as functionally selective C5aR2 ligands, exhibiting selective recruitment of β‐arrestin 2 via C5aR2, partial inhibition of C5a‐induced ERK1/2 activation and lipopolysaccharide‐stimulated interleukin‐6 release from human monocyte‐derived macrophages. Importantly, neither ligand could induce ERK1/2 activation or inhibit C5a‐induced ERK1/2 activation via C5aR1 directly. Finally, P32 inhibited C5a‐mediated neutrophil mobilisation in wild‐type, but not C5aR2 −/− mice. These functionally selective ligands for C5aR2 are novel tools that can selectively modulate C5a activity in vitro and in vivo, and thus will be valuable tools to interrogate C5aR2 function.